Potential Aquifer Exploration using Electrical Resistivity Imaging at Rumbio Jaya, Kampar, Riau - Suryadi*, Adi; Putra, Dewandra Bagus Eka; Kausarian, Husnul; Sholeh, Abdul Rahman; Tauladani, Malik; Adriyadhi, Adriyadhi (Aceh International Journal of Science and Technology, 2022)
Groundwater sustainability has become a serious issue as a water resource needed by society. Therefore, electrical Resistivity Imaging was carried out at Rumbio Jaya, Kampar, and Riau to study groundwater aquifer's electrical characteristics. The equipment used is a Geocis resistivity meter with (32) multi-electrodes alignment. Wenner configuration electrode was applied in this survey. The 2-D Electrical Resistivity inversion results indicate there are three resistivity zones; (1) Low resistivity value (0.0093 4.84 m) representing conductive clay; (2) intermediate resistivity value (1.07 171 m) indicate as potential aquifer layer; and (3) a high resistivity value (61 4000 m) occupying as bolder of rock. All the zones have different thicknesses and depths, but mostly clay layers dan boulders are shown as lenses in the aquifer of the study area. Meanwhile, the aquifer layer is found easily at a depth of 1 meter up to 30 meters.